Structural Design and Geotechnical Analysis of the Atal Tunnel: Engineering Solutions for High-Altitude Challenges - Jain, Anshul; Varma, Hridayesh (Transportation Development Research, 2025)
The Atal Tunnel, located in the Pir Panjal Range of the Himalayas in Himachal Pradesh, India, is the world’s longest highway tunnel above 10,000 feet (3,048 meters) with a length of 9.02 kilometers. This study details the tunnel’s structural components, safety features, and innovative engineering solutions, supported by data on geotechnical challenges, construction timelines, and performance metrics. This study analyzes the structural design, construction methodologies, and geotechnical challenges of the Atal Tunnel, a 9.02−km highway tunnel in the Himalayas, to evaluate its engineering solutions and impacts. Using geotechnical surveys, construction records, and performance metrics, the study employs the New Austrian Tunneling Method (NATM) framework to assess design adaptations, safety systems, and operational outcomes. The tunnel, constructed under high overburden (up to 1.9 km) and poor rock mass quality (RMR 21–40), achieved stability through adaptive NATM, with a cost escalation from ₹500 crore to ₹3,300 crore. It reduced travel distance by 46 km and time by 4–5 hours, enhancing connectivity and military logistics proving to be a great boon for the development of the country. The Atal Tunnel demonstrates innovative solutions for high-altitude tunneling, offering a model for future infrastructure projects in complex geological settings, with significant socioeconomic and strategic benefits.